PENGARUH KARAKTERISTIK PETANI DAN PERAN PENDAMPING TERHADAP KEBERHASILAN SIMANTRI DI KABUPATEN BADUNG - Bagus Aryana, Anak Agung Ngurah; Sri Budhi, Made Kembar; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.04.TAHUN 2016, 2016)
Bali Province Government is focusing to agriculture development through Program of Integrated Agriculture System (Simantri) to support the welfare of farmers. This research has purpose 1) To analyse the influence of farmers characteristic and the companion role towards the production of Simantri business in Badung regency. 2) To analyse the influence of farmers characteristic, the companion role, and the production of Simantri business towards to the success of Simantri in Badung regency. 3) To analyse the indirect effect farmer’s characteristic and companion role towards to the success of Simantri through business production Simantri in Badung regency. Data Analysis Technic used Structural Equation Modelling (SEM) with the assistance of Smart PLS Program. Result of the research showed that 1) Farmer’s characteristic and companion role has positive effect to the production business Simantri significantly in Badung Regency. 2) Thus, farmer’s characteristic, companion role and business production Simantri has positive effect significantly towards to the success of Simantri in Badung Regency. 3) There are indirect significant effect farmer’s characteristic variable and companion role towards to the success of Simantri through business production Simantri in Badung Regency.
Keywords: Simantri, Farmer’s Characteristic, Companion Role, The Success